2016
DOI: 10.5182/jaie.27.57
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Metal Ion Adsorbent from Banana Fibers and Its Adsorption Properties for Rare Metal Ions

Abstract: The synthesis of metal ion adsorbents from modified banana fibers comprising a Schiff base was investigated. The adsorption properties of a metal ion adsorbent were evaluated, and banana fiber (BF)-g-(glycidyl methacrylate)(GMA)(BF-GMA) were synthesized. A Schiff base 2,2'-{iminobis[ethane-2,1-diylnitrilo(E)methylidine]}bisphenol was synthesized via a reaction of diethylenetriamine and 5-bromo-salicyialdehyde in methanol. A metal ion adsorbent (BF-GMA(Br)) was synthesized via a reaction of the Schiff base with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…The alkali treatment removed the lignin and hemicellulose present in the non-treated banana fiber. In our previous study, we reported the SEM images of the surfaces of the banana fibers before and after being subjected to alkaline treatment 13) . The smooth surfaces of the banana fibers were found to adopt a wavy morphology after alkali treatment, which was indicative of the presence of more hydroxy groups stemming from the cellulose on the surfaces of the banana fibers.…”
Section: Adsorption Properties Of Non-treated and Alkali-treated Banamentioning
confidence: 99%
See 1 more Smart Citation
“…The alkali treatment removed the lignin and hemicellulose present in the non-treated banana fiber. In our previous study, we reported the SEM images of the surfaces of the banana fibers before and after being subjected to alkaline treatment 13) . The smooth surfaces of the banana fibers were found to adopt a wavy morphology after alkali treatment, which was indicative of the presence of more hydroxy groups stemming from the cellulose on the surfaces of the banana fibers.…”
Section: Adsorption Properties Of Non-treated and Alkali-treated Banamentioning
confidence: 99%
“…In this context, the development of environmentally friendly ion-exchange methods and the use of chelate materials for the collection and separation of metal ions are attracting growing attention from many researchers [7][8][9][10][11] . Recently, we evaluated the adsorption properties of modified banana fiber for transition metal ions 12) and rare metal ions 13) . The adsorption of cesium and strontium ions was studied using banana fibers as adsorbents 14) .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has no complexation ability with metal ions. Therefore, it has been reported on research for the adsorbents of metal ions using the modified cellulose fiber with various chelating agents such as thioglycollic acid 8) , thiolactic acid 9) , EDTA 10) and the Schiff base 11,12) .…”
Section: ( ) 43mentioning
confidence: 99%
“…Adsorption of dyes using bananaˆbers as adsorbent have been reported. 13 15) However, to our knowledge, barring our recent studies on adsorption of transition 16) and rare 17) metal ions using modiˆed bananaˆber as adsorbent, there is no other report of bananaˆber as adsorbent of metal ions.…”
Section: Introductionmentioning
confidence: 99%